Efektivitas Metode Promoting Aphasics’ Communicative Effectiveness (PACE) Terhadap Peningkatan Kemampuan Menamai Tingkat Kata Pada Pasien Afasia Broca di Karesidenan Surakarta: THE EFFECTIVENESS OF THE PROMOTING APHASICS' COMMUNICATIVE EFFECTIVENESS (PACE) METHOD ON IMPROVING THE ABILITY TO WORD NAMING LEVEL IN PATIENTS WITH BROCA'S APHASIA IN SURAKARTA PREFECTURE - Wijayanti, Rachmadani Puspitaning; Sudrajad, Kiyat; Sutanto, Alfiani Vivi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
Aphasia is a language disorder that often occurs in patients after a stroke. Broca's aphasia is a type of aphasia characterized by naming difficulties in around 30% of cases. Speech therapy is the main intervention for improving language skills. One method that can be used is the PACE (Promoting Aphasics' Communicative Effectiveness). This study aims to determine the effectiveness of the Promoting Aphasics' Communicative Effectiveness (PACE) method on improving the ability to word-level naming in patients with Broca's aphasia in Surakarta Prefecture. This research design is a single-group, pre-test-post-test, pre-experimental design. The study was conducted on eight patients with Broca's aphasia, using the total sampling technique. The instruments used were the PACE method and the word-level naming part of the TADIR test.